Analysing the Second Semester Students’ Ability in Toefl Listening Comprehension - Karta Atmaja (Eduvest - Journal of Universal Studies, 2021)
The aim of this research is to find out the second semester students’ ability in TOEFL Listening Comprehension at Sekolah Tinggi Bahasa Asing Cipto Hadi Pranoto. The method applied is the descriptive qualitative research. It revealed that the students’ ability to Longman Introductory Course Book by Deborah Phillips for TOEFL Test show the level of difficulties in Part A (short conversation) is 75 % comprising from 55 % moderate, in skill 1(restatement), skill 2 (expression of negative sentence), skill 3 (suggestion) and skill 6 (the expressions of agreement), 18 % easy in skill 5 (identifying occupation, location). However the problematic aspect in Part A is 2 % difficult to comprehend skill 4, passive statements, in Part B proves that the students’ comprehension of skill 7 (anticipating questions) is 20 % easy, and skill 8 (anticipating topics or main ideas) is 2 % moderate, in Part C shows that 11 % considered moderate to comprehend skill 11 (anticipating topics or main ideas), and 11 % easy to comprehend skill 10 (anticipating question). However, the problematic aspect in Part C is 2 % difficult to comprehend skill 12 (the order of the answer).